The effects of environmental enrichment on white matter pathology in a mouse model of chronic cerebral hypoperfusion. Issue 1 (January 2018) - Hase, Yoshiki; Craggs, Lucinda; Hase, Mai; Stevenson, William; Slade, Janet; Chen, Aiqing; Liang, Di; Ennaceur, Abdel; Oakley, Arthur; Ihara, Masafumi; Horsburgh, Karen; Kalaria, Raj N
White matter (WM) disintegration is common in the older population and is associated with vascular cognitive impairment (VCI). This study explored the effects of environmental enrichment (EE) on pathological sequelae in a mouse model of chronic cerebral hypoperfusion induced by bilateral common carotid artery stenosis (BCAS). Male C57BL/6 J mice underwent BCAS or sham surgery. One-week after surgery, mice were exposed to three different degrees of EE; either standard housing conditions (std), limited 3 h exposure to EE per day (3 h) or full-time exposure to EE (full) for 12 weeks. At 13 weeks after surgery, cognitive testing was performed using a three-dimensional 9-arm radial maze. At 16 weeks after surgery, nesting ability was assessed in each mouse immediately before euthanasia. Brains retrieved after perfusion fixation were examined for WM pathology. BCAS caused WM changes, as demonstrated by corpus callosum atrophy and greater WM disintegrity. BCAS also caused impaired nesting ability and cognitive function. These pathological changes and working memory deficits were attenuated, more so by limited rather than full-time exposure to EE regime. Our results suggest that limited exposure to EE delays the onset of WM degeneration. Therefore, the implementation of even limited EE may be beneficial for patients diagnosed with VCI.